Implementasi Kebijakan Penyelenggaraan Pembauran Kebangsaan Di Provinsi Daerah Khusus Ibukota Jakarta - S., Bastian Bahal Gaja; Anggoro, Yanuar Agung (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
In order to maintain and maintain the integrity of national unity and unity and the upholding of the sovereignty of the Unitary State of the Republic of Indonesia, it is necessary to commit all components of the nation and efforts to increase national unity and unity. Therefore, the government established Minister of Home Affairs Regulation Number 34 of 2006 concerning Guidelines for the Implementation of National Intermingling in the Regions. With this regulation, it is hoped that the issue of SARA can be avoided and overcome. The purpose of this study is to determine and analyze the implementation of the national intermingling policy as stated in the Regulation of the Governor of the Special Capital Region of Jakarta Number 5 of 2013 concerning the Establishment, Organization and Work Procedures of the National Intermingling Forum, accompanied by analyzing obstacles and efforts in its implementation. The method in this study uses a qualitative approach with a descriptive type.From the results of the study, it is known that the implementation of the Regulation of the Governor of the Special Capital Region of Jakarta Number 5 of 2013 concerning the Formation, Organization and Work Procedures of the National Intermingling Forum, has been able to run well, both from the organizational dimension, interpretation and application. The obstacles faced in the implementation of the national intermingling policy are: human resources that still need to be improved, facilities and infrastructure, namely the secretariat given to FPK which is inadequate, limited funds / budget in implementing the national intermingling program. Efforts to overcome obstacles in the implementation of national intermingling policies, among others, to improve human resources, activities such as Bimtek are also carried out by utilizing existing forums as a means of transferring knowledge and skills; to overcome obstacles in facilities and infrastructure overcome by self-help of FPK members; To overcome budget constraints, it is done by looking for sponsors / donors who will be involved in national intermingling activities held by FPK.